Hubungan Kontrol Diri dengan Fear of Missing Out (FoMO) pada Penggunaan Media Sosial: Sebuah Studi Literatur: Penelitian - Nova Lisye Sinaulan; Marssel M. Sengkey; Shinta Clara Br Tarigan; Monarika Sasaka; Dwi Sentana Br Perangin Angin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Social media has become an integral part of daily life, particularly among adolescents and young adults. However, uncontrolled use of social media can lead to a psychological phenomenon known as Fear of Missing Out (FoMO), a chronic fear of missing out on the experiences of others. One key factor believed to be associated with the intensity of FoMO is self-control. This study aims to examine the relationship between self-control and FoMO through a literature review approach. Based on an analysis of various scholarly sources, it was found that individuals with low self-control tend to experience higher levels of FoMO. The implications of these findings are significant for the development of educational strategies and psychological interventions aimed at promoting healthy social media use.